HUBUNGAN ASUPAN ZAT GIZI (PROTEIN, ZAT BESI, VITAMIN C) DAN POLA (SIKLUS, LAMA) MENSTRUASI DENGAN KADAR HEMOGLOBIN (Studi pada Remaja Putri di SMK Negeri 10 Semarang) - Ayu Silvia; Apoina Kartini; Sri Achadi Nugraheni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
At present the problem of anemia is still high. In Central Java the prevalence of anemia reaches 57.7% of the population. This is allegedly due to unhealthy food intake. In addition, abnormal menstrual patterns in adolescent girls are also thought to affect. This study aims to determine whether there is a relationship between nutrient intake and menstrual patterns with hemoglobin levels in adolescent girls at Vocational High School 10 Semarang. The study used a cross sectional design, conducted in March to July 2019, on 70 young women at Vocational High School 10 Semarang, which included inclusion criteria by purposive sampling. Data analysis using Rank Spearman and Pearson Product Moment. The analysis showed that respondents had a moderate anemia prevalence of 47.1%, a sufficient level of protein deficiency of 82.9%, iron deficiency of 98.6%, vitamin C deficiency of 98.6%, short menstrual cycles of 54.3 %, and normal menstrual periods are 52.9%. The results showed that there was a significant relationship between protein intake, iron, menstrual cycle and menstrual length with hemoglobin levels (p <0.05). But there is no relationship between vitamin C intake and hemoglobin levels (p≥ 0.05). Young women are expected to be able to maintain their intake of nutrients, especially protein and iron, and pay attention to menstrual patterns.